Identification of anti-Mycobacterium tuberculosis agents targeting the interaction of bacterial division proteins FtsZ and SepFe - Hongjuan Zhang; Ying Chen; Yu Zhang; Luyao Qiao; Xiangyin Chi; Yanxing Han; Yuan Lin; Shuyi Si; Jiandong Jiang (Elsevier, 2023)
Tuberculosis (TB) is one of the deadly diseases caused by Mycobacterium tuberculosis (Mtb), which presents a significant public health challenge. Treatment of TB relies on the combination of several anti-TB drugs to create shorter and safer regimens. Therefore, new anti-TB agents working by different mechanisms are urgently needed. FtsZ, a tubulin-like protein with GTPase activity, forms a dynamic Z-ring in cell division. Most of FtsZ inhibitors are designed to inhibit GTPase activity. In Mtb, the function of Z-ring is modulated by SepF, a FtsZ binding protein. The FtsZ/SepF interaction is essential for FtsZ bundling and localization at the site of division. Here, we established a yeast two-hybrid based screening system to identify inhibitors of FtsZ/SepF interaction in M. tuberculosis. Using this system, we found compound T0349 showing strong anti-Mtb activity but with low toxicity to other bacteria strains and mice. Moreover, we have demonstrated that T0349 binds specifically to SepF to block FtsZ/SepF interaction by GST pull-down, fluorescence polarization (FP), surface plasmon resonance (SPR) and CRISPRi knockdown assays. Furthermore, T0349 can inhibit bacterial cell division by inducing filamentation and abnormal septum. Our data demonstrated that FtsZ/SepF interaction is a promising anti-TB drug target for identifying agents with novel mechanisms.